Lymphocutaneous sporotrichosis - Vijayaragavan Kutty; Balasankar Soundaian; Balasubramanian Jeyaraman; Sathishkumar Manisekaran (Wolters Kluwer Medknow Publications, 2023)
Sporotrichosis is a chronic subcutaneous mycosis caused by a fungus, Sporothrix schenckii complex. The first case in India was reported by Ghosh in 1932. The disease is prevalent primarily in the sub-Himalayan region, North-eastern states, and parts of Karnataka. Mostly seen in adults, it uncommonly presents in children over the face and limbs either as fixed cutaneous or lymphocutaneous form. Here, we present a case of 3-years-old boy hailing from Southern Tamil Nadu with multiple nodular lesions in linear fashion over the right upper limb. It was diagnosed as a case of lymphocutaneous sporotrichosis that developed following cut injury over the right index finger. We publish this case as it is rare to occur in this geographic location.